Third Five Year Plan of Chickamagalur District Government of Mysore - Planning Commission (Planning Commission)
The Chickmagalur District consists of seven taluks with 32 hobbies and 1,115 villages. There are two Subdivisions, Chickmagalur and Tarikere and nine Municipalities in the District, viz., Chickmagalur, Kadur, Tarikere, Birur, Ajjampura, Mudigere, Koppa, Narasimharajapura and Sringeri. One hundred and ninety-six Village Panchayats and seven Taluk Boards have been constituted under the Mysore Village Panchayat and Local Boards Act, 1959.
Government of Mysore, Planning, Housing, and Social Welfare Department